Epithelial down‐regulation of the miR‐200 family in fibrostenosing Crohn's disease is associated with features of epithelial to mesenchymal transition. Issue 11 (6th September 2018) - Mehta, Shameer J.; Lewis, Amy; Nijhuis, Anke; Jeffery, Rosemary; Biancheri, Paolo; Di Sabatino, Antonio; Feakins, Roger; Silver, Andrew; Lindsay, James Oliver
Abstract: Intestinal mesenchymal cells deposit extracellular matrix in fibrotic Crohn's disease (CD). The contribution of epithelial to mesenchymal transition (EMT) to the mesenchymal cell pool in CD fibrosis remains obscure. The miR‐200 family regulates fibrosis‐related EMT in organs other than the gut. E‐cadherin, cytokeratin‐18 and vimentin expression was assessed using immunohistochemistry on paired strictured (SCD) and non‐strictured (NSCD) ileal CD resections and correlated with fibrosis grade. MiR‐200 expression was measured in paired SCD and NSCD tissue compartments using laser capture microdissection and RT‐qPCR. Serum miR‐200 expression was also measured in healthy controls and CD patients with stricturing and non‐stricturing phenotypes. Extra‐epithelial cytokeratin‐18 staining and vimentin‐positive epithelial staining were significantly greater in SCD samples ( P  = 0.04 and P  = 0.03, respectively). Cytokeratin‐18 staining correlated positively with subserosal fibrosis ( P  < 0.001). Four miR‐200 family members were down‐regulated in fresh SCD samples (miR‐141, P  = 0.002; miR‐200a, P  = 0.002; miR‐200c, P  = 0.001; miR‐429; P  = 0.004); miR‐200 down‐regulation in SCD tissue was localised to the epithelium ( P  = 0.001‐0.015). The miR‐200 target ZEB1 was up‐regulated in SCD samples ( P  = 0.035). No difference in serum expression between patient groups was observed. Together, these observations suggest the presence of EMT in CD strictures and implicate the miR‐200 family as regulators. Functional studies to prove this relationship are now warranted.